A histologic study of tissue reaction towards an alloplastic implant material "Proplast" in rabbits - Lo, Henry
Small pieces of "Proplast" implant material were placed in artificially created wounds in 8 rabbit mandibles. The animals were sacrificed at weekly intervals from the second to the ninth week. Sections of the implant site were observed under the microscope. The result shows that Proplast was well tolerated without unfavorable tissue reaction. Bone growth was observed throughout the implant interstices starting from the seventh week.